(untitled) (The Pakistan Development Review, 1985)
According to Paul Streeten [101, the relationship between poverty eradication and reducing income inequalities is still an unsettled question. He mentions empirical studies of eleven countries. In ten of these countries, poverty and inequality move in the same direction, both increasing (Brazil, Mexico, Indonesia) or both declining (Korea, Taiwan, Sri Lanka, Costa Rica, Yugoslavia, China and Israel). The only exception is perhaps Kuwait, where poverty (of Kuwaiti citizens, but not of the large group of immigrant workers) has been reduced, while inequality has increased (explanation: oil wealth).